1994
DOI: 10.1108/09596119410065914
|View full text |Cite
|
Sign up to set email alerts
|

Hotel Security: The Needs of the Mature Age Market

Abstract: The mature age market segment in Australia have increased leisure time and disposable income. Many hotels are trying to increase occupancies, particularly in low season, by attempting to attract this market segment. Reports on a survey of the security needs and perceptions of the mature guests and compares the results with research in other settings. The respondents′ views about emerging security practices are also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…The location of an establishment is one of the most critical decisions in the hospitality industry (Chou et al, 2008), and it is common practice for hotels to update security features when the surrounding location becomes less safe (Feickert et al, 2006). The safety and security of the hotel and surrounding areas is of great importance to guests (Lockyer, 2005), and the location of a hotel has also been shown to trigger thoughts regarding personal security (Shortt and Ruys, 1994). Research has shown that security concerns such as public order issues and crime are crucial when selecting a location (Chou et al, 2008).…”
Section: H1mentioning
confidence: 99%
“…The location of an establishment is one of the most critical decisions in the hospitality industry (Chou et al, 2008), and it is common practice for hotels to update security features when the surrounding location becomes less safe (Feickert et al, 2006). The safety and security of the hotel and surrounding areas is of great importance to guests (Lockyer, 2005), and the location of a hotel has also been shown to trigger thoughts regarding personal security (Shortt and Ruys, 1994). Research has shown that security concerns such as public order issues and crime are crucial when selecting a location (Chou et al, 2008).…”
Section: H1mentioning
confidence: 99%
“…One common mistake marketers often make in developing strategy is believed to be the use of stereotypical profiles of older persons. The mature consumer market consists of older people who exhibit a great deal of variability with respect to the way they look, think and act (Moschis et al, 1997;Shortt and Ruys, 1994;Caballero and Hart, 1996;Dychtwald, 1997). Because the effectiveness of marketing strategies and programs varies by type of segment and type of product, decision makers should rely primarily on information about older consumers' responses to marketing offerings, which are specific to the product or service being marketed as well as to the segment of interest (Moschis et al, 1997).…”
Section: Marketing To Maturitymentioning
confidence: 99%
“…The use of single items to measure attribute-level and overall satisfaction is common in travel and tourism studies. [82][83][84] Rather than deviate from this norm, standard procedures used in travel and tourism studies were followed. Furthermore, the Beijing group included only 45 respondents.…”
Section: Study Methodologymentioning
confidence: 99%